Pathways linking school bullying and psychotic experiences: Multiple mediation analysis in Chinese adolescents and young adults - Chen, Lu Hua; Toulopoulou, Timothea (Frontiers in Psychiatry, 2022)
It is found that people with psychotic experiences have a 4-fold increased risk of developing a psychotic disorder later in life. Indeed, accumulating evidence has suggested that the association between school bullying and psychotic experiences works linearly. Previous studies are mainly carried out in a Western context, and only seldomly do studies address whether the association exists in the Chinese population and the related psychological and cognitive mechanisms. Therefore, we carried out the current study to address this gap in the literature focusing on the lifelong school bullying experiences of Chinese adolescents and young adults. We examined them in relation to psychotic experiences while assessing the mediating role of self-esteem, the personality trait of neuroticism, and a cognitive bias in thinking called interpretation bias. We found that multiple victimizations were quite common in Hong Kong secondary schools. In addition to a significant association between school bullying and psychotic experiences, we found partial mediating effects of proposed psychological and cognitive mediators in constructed multiple mediation models utilizing bootstrapping approach. Specifically, bullying quantity reflecting the number of victimizations, had its association with psychotic experiences partially mediated by the personality trait of neuroticism. In contrast, bullying duration reflecting the lasting of victimization was associated with psychotic experiences partially mediated by the personality trait of neuroticism and interpretation bias. Our findings enhance our knowledge of mechanisms underpinning the psychosis spectrum development and have implications for school-based intervention programs targeting bullying victims in Hong Kong.